2009
DOI: 10.1007/s11334-009-0085-4
|View full text |Cite
|
Sign up to set email alerts
|

A development methodology for embedded systems based on RT-DEVS

Abstract: This work is concerned with modelling, analysis and implementation of embedded control systems using RT-DEVS, i.e. a specialization of classic discrete event system specification (DEVS) for real-time. RT-DEVS favours model continuity, i.e. the possibility of using the same model for property analysis (by simulation or model checking) and for real time execution. Special case tools are reported in the literature for RT-DEVS model analysis and design. In this work, temporal analysis of a model exploits a transla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…We reproduced the results that were obtained manually in [4] with our automatic translation and showed that the tool is applicable to models of relatively simple real-time systems with parallel interacting processes. Further work includes formal proof of the correctness of the algorithm based on [3] and testing the tool on practical examples of real-time systems.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…We reproduced the results that were obtained manually in [4] with our automatic translation and showed that the tool is applicable to models of relatively simple real-time systems with parallel interacting processes. Further work includes formal proof of the correctness of the algorithm based on [3] and testing the tool on practical examples of real-time systems.…”
Section: Discussionmentioning
confidence: 69%
“…Some more complex tests were aimed to simulate the whole process of verification of a system defined by a UML statechart diagram. Below we present the results of our experiments with the model of traffic lights control system described in [4].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, Yakindu does not provide formal verification capability. To bridge the gap between system modeling and formal verification, efforts are made from research community to transform system modeling specifications/languages, such as UML (unified modeling language) statecharts [13], [20], hierarchical timed automata (HTA) [5], discrete event system specification for real-time (RT-DEVS) [8], and parallel object-oriented specification language (POOSL) [18], to UPPAAL timed automata. Yakindu statecharts are similar to UML statecharts, but have major semantics differences [2].…”
Section: Introduction and Related Workmentioning
confidence: 99%